2008
DOI: 10.1021/bi702428q
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Peptide Antagonists to Glycoprotein Ibα That Selectively Inhibit von Willebrand Factor Dependent Platelet Aggregation

Abstract: GPIbalpha is an integral membrane protein of the GPIb-IX-V complex found on the platelet surface that interacts with the A1 domain of von Willebrand factor (vWF-A1). The interaction of GPIbalpha with vWF-A1 under conditions of high shear stress is the first step in platelet-driven thrombus formation. Phage display was used to identify peptide antagonists of the GPIbalpha-vWF-A1 interaction. Two nine amino acid cysteine-constrained phage display libraries were screened against GPIbalpha revealing peptides that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
(47 reference statements)
2
21
0
Order By: Relevance
“…The patients who presented with ICH as the first manifestation of the ITP were excluded from treatment/cost analysis. As in previous studies, 2,5,6 head trauma and hemorrhagic manifestations (beyond mild cutaneous) were significant risk factors for ICH and, in the case of more bleeding manifestations, increased mortality. In contrast to other studies, the authors found no relationship between concurrent nonsteroidal anti-inflammatory drug use, wet purpura, and gastrointestinal or vaginal bleeding, but this may be due in part to the limitations of retrospective reporting in a survey study.…”
Section: Conflict-of-interest Disclosure: the Authors Declare No Compsupporting
confidence: 74%
See 1 more Smart Citation
“…The patients who presented with ICH as the first manifestation of the ITP were excluded from treatment/cost analysis. As in previous studies, 2,5,6 head trauma and hemorrhagic manifestations (beyond mild cutaneous) were significant risk factors for ICH and, in the case of more bleeding manifestations, increased mortality. In contrast to other studies, the authors found no relationship between concurrent nonsteroidal anti-inflammatory drug use, wet purpura, and gastrointestinal or vaginal bleeding, but this may be due in part to the limitations of retrospective reporting in a survey study.…”
Section: Conflict-of-interest Disclosure: the Authors Declare No Compsupporting
confidence: 74%
“…5 Now, the riddle of OS-1's mechanism of action has been solved, and the solution appears in this issue of Blood. McEwan et al determined the crystal structure of OS-1 in complex with GPIb␣ and found that, unlike the situation with RGD-or KGDbased inhibitors of ␣ IIb ␤ 3 , OS-1 does not mimic the binding of VWF to GPIb␣.…”
Section: The Proof Is In the Crystal --------------------------------mentioning
confidence: 99%
“…Because PCA significantly inhibited ristocetin-induced platelet aggregation, which occurs in a vWF A1-GP Ib␣-dependent manner in the absence of high shear stress, the third possibility may be excluded. Incidentally, blockers of vWF A1-GP Ib␣ interaction that have been reported were mostly antibodies or peptide mimetic (Benard et al, 2008;Clemetson and Clemetson, 2008;Kiefer and Becker, 2009). Few studies have been published on small molecules that have anti-SIPA or vWF-GP Ib blocking effects to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…As proof of this concept, a short cyclic peptide, CTERMALHNLC, which binds GPIbα, potently inhibits vWF binding not through competitive inhibition but by preventing formation of a ligandreceptive structural conformation. 83,84 An alternative strategy targeting the ADP-P2Y1/P2Y12 activation pathway is the use of a soluble form of CD39 (solCD39), an ectonucleoside triphosphate diphosphohydrolase. 85 This approach uses the ability of CD39 to hydrolyze ADP, dissimilar to the current ADP-P2Y12 drugs clopidogrel, prasugrel, and ticagrelor that block ADP-mediated platelet activation by binding to the receptor directly.…”
Section: Future Targets For Antiplatelet Therapymentioning
confidence: 99%